The Influence of Work Discipline on Employee Job Satisfaction with Incentives as an Intervening Variable - Jopinus Saragih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The results of this research show. (1) It can be seen that the adjusted R square value is 0.767 or 76.7%. This shows that incentives (Z) and work discipline (X) can explain job satisfaction (Y) by 76.7%, the remaining 23.3% (100% - 76.7%) is explained by other variables outside the research model This. (2) The results of the t test (Partial) show that the value obtained is tcount (4,251) > ttable (2.048), likewise with a significance value of 0.00 < 0.05, it can be concluded that the first hypothesis is accepted, meaning that the work discipline variable(X) has a positive and significant effectagainst incentives (Z).(3) The results of the t test (Partial) show that the value of tcount (4.221) > ttable (2.048), and the significance value is 0.00 < 0.05, so it can be concluded that the second hypothesis is accepted, meaning that work discipline(X) has a significant effecton job satisfaction (Y). (4) The results of the t test (Partial) show that tcount(7.162) > ttable (2.048), and the significance value is 0.00<0.05, so it can be concluded that the third hypothesis is accepted, meaning that incentive (Z)significant effecton job satisfaction (Y) (5) The results of path analysis show that the direct influence of variable X on variable Y2 is 0.395. Meanwhile, the indirect influence through variable Z is 0.620 x 0.670 = 0.415. From the calculation results, it can be seen that the indirect influence through variable Z is greater than the direct influence on variable Y.